Pattern of Injuries in Fatal Head Trauma Due to Road Traffic Accidents - M. N. Rajamani Bheem Rao; A. Nirmala; R. Raguram (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Head trauma is considered to be the major cause of death in road traffic accidents. According toworld health organisation, about 1.24 million deaths occur due to road traffic crashes. Particularly, the treatmentsfor head injury in the older aged people seems to be more complicated when compared to younger and middle agegroups. The aim of this study is to analyse and identify the significance and outcome of head trauma due to roadtraffic accidents of various age groups.Methods: This study was conducted on Madras Medical College, in the Department of Forensic Medicine,Chennai . a total of 200 fatal head injury case autopsies were performed. After obtaining the necessary and relevantinformation about the deceased, a thorough autopsy was performed and the findings were recorded.Result: Out of 200 cases, 83% were men and 44.5% were recorded to be between 31-50 age group. Fissure fractureof skull was found to be most prevalent (40.5%) and subdural haemorrhage was the common findings in headinjury (95%).Conclusion: The resultsof our study showed that most of the people who had accidents were pedestrian and twowheeler driving persons.